Does Income-Increasing Earnings Management Enhance Tax Aggressiveness? The Moderating Role of The Corporate Governance Mechanism - Zalfaa', Vina; Roekhudin; Atmini, Sari (Accounting Department,, 2022)
Purpose — This study examines and analyzes the effect of income-increasing accrual and natural earnings management on tax aggressiveness with institutional ownership as a moderating variable. Design/methodology/approach — The research population is manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2019. The research sample selection method used is the purposive sampling method. There are 84 observations (firm-year) for income-increasing accrual earnings management and 81 observations (firm-year) for income-increasing natural earnings management. Data analysis is conducted using Moderated Regression Analysis (MRA). Findings — As predicted, this study finds a positive effect of income-increasing accrual earnings management and a negative effect of income-increasing natural earnings management on tax aggressiveness. However, this study cannot prove that institutional ownership moderates the relationship between income-increasing accrual and income-increasing natural earnings management on tax aggressiveness. Practical implications — Our study can be used as evidence for the Directorate General of Taxes and the Financial Services Authority that implementing good corporate governance in companies may not necessarily reduce the practice of tax and financial reporting aggressiveness. This can be used as a reference for improving Indonesia's tax and accounting regulations and policies. Originality/value — This study presents income-increasing accrual and natural earnings management activities as well as corporate tax aggressiveness activities in manufacturing companies in Indonesia. Hopefully, this can be used as an evaluation to improve existing tax and accounting regulations and policies in Indonesia.